Tyranny of the weak : North Korea and the world, 1950-1992 - Armstrong, Charles K. (Ithaca : Cornell University Press, 2013)
From the invasion that set off the Korean War in June 1950 to the collapse of the Soviet Union in 1991, Armstrong shows how, despite its objective weakness, North Korea has managed for much of its history to deal with the outside world to its maximum advantage. Insisting on a path of'self-reliance' since the 1950s, North Korea has continually resisted pressure to change from enemies and allies alike. A worldview formed in the crucible of the Korean War and Cold War still maintains a powerful hold on North Korea in the twenty-first century, and understanding those historical forces is as urgent today as it was sixty years ago.
The unfinished war, 1950-1953 -- Post-war reconstruction and a declaration of self-reliance, 1953-1955 -- A singular path : North Korea in the socialist community,1956-1963 -- The anti-imperialist front, 1963-1972 -- Breaking out : engaging the first and third worlds, 1972-1979 -- A new generation and a new cold war, 1980-1984 -- The sun sets in the east, 1985-1992 -- Epilogue : tyranny of the weak, tyranny of the strong.
Includes bibliographical references : pages 295-302 and index.
Keywords: Korea (North) -- Foreign relations; Korea (North) -- Politics and government